Saluran Pemasaran Ikan Cakalang Hasil Tangkapan Kapal Pole And Line di Pelabuhan Belang Kabupaten Minahasa Tenggara - Kadir, Risman; Tuli, Munirah; Baruadi, Alfi Sahri Remi (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
This study aims to analyze the marketing chain of skipjack tuna (Katsuwonus pelamis) caught by pole and line vessels at Belang Port, Southeast Minahasa Regency. The research method used is a survey with a descriptive approach, involving fishers, middlemen, and retailers as respondents. Primary data were obtained through interviews, observations, and documentation, while secondary data were collected from relevant literature. The results show that the marketing chain of skipjack tuna involves three main channels: (1) zero-level channel (fishers directly to consumers), (2) first-level channel (fishers to retailers), and (3) second-level channel (fishers to middlemen and then to retailers). The highest marketing margin is received by retailers, while the lowest is received by fishers. Marketing efficiency is influenced by several factors, including limited capital, infrastructure, market information access, and the dependence of fishers on middlemen. This study recommends strengthening fisher institutions, improving market access, and providing training and empowerment in marketing to enhance efficiency and the welfare of fishers.